Uji Antagonis Cendawan Isolat Lokal Terhadap Fusarium spp, Penyebab Penyakit Layu Pada Tanaman Kentang (Solanum tuberosum L ) Secara In Vitro. - Hilda Karim; Yusminah Hala; Andi Irma Suryani; Risma Syam (Universitas Negeri Makassar, 2023)
This research aims to: (a) determine the number of fungal isolates capable of inhibiting the growth of Fusarium sp. in vitro, (b) determine the percentage of inhibitory activity of the antagonistic fungal isolates against Fusarium sp. in vitro, (c) identify the morphological characteristics of the top three antagonistic fungal isolates from the rhizosphere of potato plants (Solanum tuberosum L.). To achieve these objectives, the in vitro experimental testing was conducted at the Biology Laboratory of Makassar State University. The research results showed that: (a) based on macroscopic and microscopic morphological characteristics, the fungi isolated from potato plants were identified as Fusarium oxysporum f.sp. solanaceae. (b) There were seven isolates capable of inhibiting the growth of F.o.sp. solanaceae, namely Aspergillus sp (green), Aspergillus sp (black), Eupenicillium sp, Chaetomium sp, Paecilomyces sp, and Monilia sp. The percentage of their inhibitory activity was 54.71%, 73.13%, 36.82%, 55.01%, 50.66%, 46.53%, and 43%, respectively. (c) The morphological characteristics of the top three antagonistic fungal isolates were as follows: 1. Black Aspergillus sp had a black colony with a solid texture and very rapid growth. The hyphae were septate and non-branched, and the spherical conidia were black. 2. Green Aspergillus sp had a colony with dark green (inner), light green (middle), and white (outer) regions. The conidia were spherical, with a solid and slightly elevated texture, spreading in all directions. The hyphae were septate and non- branched. 3. Chaetomium sp had a white cotton-like colony with a fine and thick texture, spreading in all directions. The conidiophores were irregularly branched, and the hyphae were septate.